2007
DOI: 10.1007/s00011-007-6135-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of mast cells in rheumatoid synovial tissue results in production of TNF-α, IL-1β and IL-1Ra

Abstract: Synovial mast cells produce proinflammmatory cytokines and may thus contribute to the inflammation in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 22 publications
5
42
0
4
Order By: Relevance
“…This difference might be attributed to the fact that the latter authors used immunohistochemistry for the detection of mast cells. In the present study, mast cells were observed close to the periphery of cystic lesions, in agreement with other studies suggesting that the presence of tryptase-positive mast cells at the periphery of these lesions might contribute to both lesion expansion and bone resorption (4,12) as a result of their ability to promote inflammatory reaction by inducing the production of TNF-a, IL-1b (13), and chemokines such as MIP-1a and MCP-1 (16). Although MCP-1 levels were higher in granulomas and MIP-1ß levels were higher in cysts, the expression of both chemokines was significantly higher in these lesions when compared with healthy pulp tissues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This difference might be attributed to the fact that the latter authors used immunohistochemistry for the detection of mast cells. In the present study, mast cells were observed close to the periphery of cystic lesions, in agreement with other studies suggesting that the presence of tryptase-positive mast cells at the periphery of these lesions might contribute to both lesion expansion and bone resorption (4,12) as a result of their ability to promote inflammatory reaction by inducing the production of TNF-a, IL-1b (13), and chemokines such as MIP-1a and MCP-1 (16). Although MCP-1 levels were higher in granulomas and MIP-1ß levels were higher in cysts, the expression of both chemokines was significantly higher in these lesions when compared with healthy pulp tissues.…”
Section: Discussionsupporting
confidence: 93%
“…However, little is known about the interaction between these cells, cytokines, and other inflammatory elements in periapical lesions. Mast cells and macrophages are tissueresident cells known to play an important role in the development of inflammatory reactions as a result of their capacity to release TNF, thus modulating local inflammation (13). On the other hand, some investigators believe that mast cells are part of a negative feedback mechanism in periapical granulomas, and that the direct action of histamine on T lymphocytes might inhibit the production of IL-2 and IFN-g, thus suppressing the activity of T cells in response to antigens (11,14).…”
mentioning
confidence: 99%
“…This concept is supported by findings in experimental arthritis models, as well as by data in human RA, including the demonstration that synovial mast cells are important producers of TNF, IL-1␤, and IL-17 (15)(16)(17)(18). In contrast, the presence and function of mast cells have not been assessed in SpA.…”
mentioning
confidence: 80%
“…128, 129 Increased levels of proinflammatory cytokines, such as IL6, IL17, and TNFα, have also been associated with rheumatoid arthritis and mast cells have been identified as the main source of IL17 expression. 130, 131 …”
Section: Mast Cellsmentioning
confidence: 99%